Industrial constructions the sources of German industrial power - Herrigel, Gary (Structural analysis in the social sciences, 1996)
The upshot of Herrigel's argument is not only that there were several processes of industrialization that occurred simultaneously in German history, but that there has never been a single boundary between industry and the rest of society and politics in Germany; there have always been several. Theoretically, the book rejects the fundamentally unitary conceptions of industrialization and political economy underlying the Gerschenkronian, Schumpetarian, and Chandlerian principles that shape the traditional organized capitalism research program in the study of the German industrial economy and argues for a more open social constructivist approach